Comparison and evaluation of different seed extracts of Trachyspermum ammi for immunomodulatory effect on cell-mediated immunity through delayed-type hypersensitivity assay skin thickness method - Siddiqui, Mohammad Jamshed Ahmad; Aslam, Adeel; Khan, Tanveer (Wolters Kluwer - Medknow, 2019)
Traditionally Trachyspermum ammi has been used for the treatment of immune disease such as rheumatism. The aim and objective of this study was to find the immunostimulant effect of three different extracts of T. ammi seeds. To assess the immunomodulatory effect, delayed-type hypersensitivity (DTH) assay method was used and by the DTH assay, the effect of T. ammi on the skin thickness of rats was estimated. Seeds of T. ammi were extracted using three different solvents—n-hexane, chloroform, and methanol—by using Soxhlet apparatus. To find the exact dose for administration, acute toxicity test was performed using crude methanolic extract at a dose of 400, 800, 1600, and 3200 mg/kg. After acute toxicity test, 500 mg/kg dose was determined as safe for therapeutic effect and immunomodulatory effect was evaluated at this dose. Dose of 500 mg/kg was administered to Wistar rats daily for 14 days and skin thickness of rats was measured at 24, 48, and 72 h. Results were obtained from six groups of rats, which were positive control group, negative control group, and the groups receiving the test drugs. Standard drug was the combination of sodium selenite, vitamin E, and sodium chloride and it showed more positive results as compared to that of test drug. Furthermore, among the three extracts, methanol extract showed more effectiveness on skin thickness. There was a meaningful difference in the skin thickness of rats when the skin thickness was measured on the 2nd and 14th day of activity.